IMPACTS OF INTERPERSONAL METAPHOR ON GRAMMATICAL INTRICACY AND LEXICAL DENSITY IN THE TEXT OF PRESIDENTIAL DEBATE BETWEEN BARRACK OBAMA AND MITT ROMNEY - Aritonang, Deddy Kristian (TABULARASA, 2014)
The objectives of the study are (1) to identify types of interpersonal metaphor used in the text of presidential debate between Barrack Obama and Mitt Romney, (2) to describe the impacts of interpersonal metaphor grammatical intricacy (GI) and lexical density (LD) in the text of presidential debate between Barrack Obama and Mitt Romney with reference to congruent coding, (3) to explain the ways interpersonal metaphor have impacts on GI and LD in the text of presidential debate between Barrack Obama and Mitt Romney. The findings reveal that both types of interpersonal metaphor namely metaphor of modality and metaphor of mood are found. In terms of metaphor of modality, the three values namely high, medium and low are identified as the following proportions: 18 utterances (25.71%) with high value, 28 utterances (40%) with medium value and 8 utterances (11.42%) with low value. Meanwhile the rest is metaphor of mood which is realized in questions as many as 14 utterances (20%) and command which occur twice (2.85%). All of metaphor of modality and metaphor mood have the higher ratio of GI compared to the congruent forms. As for LD, the result was various; this is to say that to one side, the presence of interpersonal metaphor in some utterances cause the utterances to have higher ratio of LD than that of the congruent codings. On the other side, the ratio of LD in some of the congruent codings are higher than that of some of the interpersonal metaphor utterances.